Spinal Intrathecal Actinomycosis Causes Multisegmental Root Failure: A Case Report - Wang, Yanying; Ren, Xinyu; Shen, Dongchao; Mao, Chenhui; Wang, Han; Peng, Bin; Gao, Jun; Cui, Liying (Frontiers in Neurology, 2020)
Actinomycosis is a slowly progressing infection caused by Actinomyces species, which consists of filamentous gram-positive bacteria. Intraspinal actinomycosis is very rare and most of the previous cases presented with epidural lesions. Only two cases of intrathecal actinomycosis have been described. We reported a case of intrathecal actinomycosis in a 46-year-old woman. Our patient presented with multisegmental root failure, which was different from previous intrathecal cases mainly involving the spinal cord. The manifestations, cervical MR imaging results, biopsy and histopathological features, and treatment history of the patient were reviewed. Clinical features of this disease resemble intraspinal neoplasms, other infectious processes, and granulomatous diseases, thus being difficult to diagnose preoperatively. Histopathological evidence from the biopsy is important for timely diagnosis. Early diagnosis and treatment may greatly improve the prognosis.